2022
DOI: 10.1155/2022/9516922
|View full text |Cite|
|
Sign up to set email alerts
|

A Cohort Study of Surgical Indexes, Postoperative Complications, Recovery Speed, and Prognosis of Stanford Type A Aortic Dissection Compared with Traditional Sun’s Operation

Abstract: Objective. The objective is to explore the surgical index, postoperative complications, recovery speed, and prognosis of Stanford type A aortic dissection (AD) compared with traditional ’Sun’s operation. Methods. One hundred patients with Stanford type A AD treated from February 2018 to February 2021 were enrolled in our hospital. Patients were randomly divided into control and research group. The former group underwent traditional Sun’s surgery, and the latter group underwent combined debranching surgery. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%